Challenges in Music Education: Teachers’ Competencies, Teaching Styles and ICT Integration - Sun, Haoyue; Abramauskienė, Jolanta (Pedagogika, 2025)
This article focuses on music education and explores the teaching challenges, difficulties, required competencies, education system and use of ICT integration, ways to develop learners' attitudes towards music and collaborative methods. Qualitative research methods were used in the study. The research showed that due to the changes in the educational model, music education has become complex, requiring teachers to use ICT and adapt their teaching style to enhance learners' experience and engagement.